2021
DOI: 10.3389/fped.2021.716608
|View full text |Cite
|
Sign up to set email alerts
|

Sleep and Coping in Early Childhood During the COVID-19 Pandemic

Abstract: Sleep disturbances in early childhood are associated with mood and anxiety disorders. Children also exhibit sleep disruptions, such as nighttime awakenings, nightmares, and difficulties falling asleep, in conjunction with adverse events and stress. Prior studies have examined independently the role of sleep on adaptive processing, as well as the effects of stress on sleep. However, how childhood sleep and children's adaptive behavior (i.e., coping strategies) bidirectionally interact is currently less known. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 51 publications
1
10
1
2
Order By: Relevance
“…25 Also Lokandwala et al found changes in sleeping patterns during the pandemic. 27 The reason for the discrepancy between our ndings (no changes in sleep quality) and the existing reports may lie in different methodology used. However, it has to be noted that the determinants of children's sleep behavior are scarcely understood, with moderate evidence for screen-time.…”
Section: Discussioncontrasting
confidence: 86%
“…25 Also Lokandwala et al found changes in sleeping patterns during the pandemic. 27 The reason for the discrepancy between our ndings (no changes in sleep quality) and the existing reports may lie in different methodology used. However, it has to be noted that the determinants of children's sleep behavior are scarcely understood, with moderate evidence for screen-time.…”
Section: Discussioncontrasting
confidence: 86%
“…Nineteen studies (4 cohort, 14 cross-sectional and 1 qualitative) reported changes in sleep quality from before to during the COVID-19 lockdown. Eight (one cohort, six cross-sectional and one qualitative)39 40 47 71 80–83 of them observed a decrease, five (one cohort and four cross-sectional)27 51 73 74 79 observed an increase and six (two cohort and four cross-sectional)26 53 76–78 84 observed no significant change in sleep quality.…”
Section: Resultsmentioning
confidence: 89%
“…Studies from the UK and Poland reported that children slept less during the lockdown than before the lockdown 51 54. Two multicountry studies and studies from Spain, Australia, the USA, Portugal and China did not observe any significant difference in sleep duration among children and adolescents from before to during the lockdown 3 20 26 40 49 55 56 75 76…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…A specific questionnaire was arranged for the survey including a modified version of the Sleep Disturbance Scale for children (SDSC) and completed by caregivers. Also Lokandwala et al found changes in sleeping patterns during the pandemic [27]. This study used an Actiwatch Spectrum Plus watch to track sleeping behavior and compared it to data sampled from the same subject before the pandemic.…”
Section: Other Outcomesmentioning
confidence: 99%